The effect of relying on One Lingua Franca in engaging In effective Global Online International Trade. - Kusedyo, Fanuel S. (Midlands State University., 2017)
The focus of the study was to challenge the continued dominance of English as a Lingua Franca, which is what (Lanvers, 2011) termed as the hegemony of English. The background of the study is that this is the 21st century whereby the traditional trade barriers caused by geographical locations have been eliminated due to technology. The internet has come a long way to alleviate the communication barrier, however the diversity of world languages still remain as a challenge. This study assessed the existing languages used for international trade in Zimbabwe, to find out how locals embraced language and cultural diversity and inclusion. The objectives of the study were to come up with recommendation for a language policy as well as recommend the best time or age to introduce foreign language learning in the country. Zimbabwe has sixteen official languages; however English appears to be the only language used for online international trade despite the fact that statistics reveal that only 27% of the global internet searches are generated by English speakers The content to searchers ratio for English is 203%, implying that there currently is too much English content online, whereas 73% of the searches are not even looking for English content. The literature review featured people like Clark, Needley and Bada who advocated and maintained that English is the global language for trade as well as views from Holmqvist and Vaerenberg who strongly opposed this position. The literature attempted to find out if similar researches were done on Zimbabwe, and found that all the prior researches done on languages originated from faculties of arts, humanities and linguistic and were premised on issues about minority languages discrimination and not from the dimension of how languages impact business, as languages should be an integral part of the business school curriculum. The study managed to articulate all its objectives, came up with some recommendations on how to address them. A qualitative research design approach was used and a survey was adopted. The study population was 325, made up of students studying foreign languages at four of the major language centres in Harare. The sample used amounted to 100 respondents and the response rate was 86%. The triangulation method was used by studying the people learning language as well as a control group which consisted of ordinary people and business people. Interviews, observations, questionnaires and documentary analysis were used to elicit information pertaining to effects of being monolingual and benefits of being multi lingual. The research finding were analyzed in line with the objectives and SPSS data analysis and excel software were used. The results were presented in the form of tables, charts and descriptive analysis. The findings established that most Zimbabweans are in fact bilingual and trilingual however most of the second or third languages are not International Lingua Francas. Very few Zimbabwean appreciate the power of having a foreign language on their website so as to tap on the vast market of foreigners who are out there searching for our goods. The study recommends the introduction of global Lingua Francas to the academic curriculum as well as the policies to encourage the use of multiple languages especially on websites so as to enable the access of untapped international markets. A recommendation of an area for further study was made on the feasibility of skills export to non English speaking countries, given the fact that Zimbabweans are highly skilled and their movement into the Diaspora is mainly to English speaking countries due to issues of communication.